Epidemiology of alveolar echinococcosis with particular reference to China and Europe. - Vuitton, D. A.; Zhou, H.; Bresson-Hadni, S.; Wang, Q., A.; Piarroux, M.; Raoul, F.; Giraudoux, P. (CCSD, 2003)
International audience Human alveolar echinococcosis (AE), caused by the metacestode of the fox tapeworm Echinococcus multilocularis, is the most pathogenic zoonosis in temperate and arctic regions of the northern hemisphere. Prospective collection of human cases in some areas and mass screenings using ultrasound imaging and confirmation with serological techniques have markedly improved our knowledge of the epidemiology of the disease in humans during the past two decades. Transmission occurs when eggs of the tapeworm, excreted by the final hosts (usually foxes but also dogs, wolves and cats), are ingested accidentally by humans or during normal feeding by a variety of rodents and small lagomorphs. However, the species of host animals differ according to regional changes in mammalian fauna. This review mostly focuses on epidemiology of alveolar echinococcosis in those parts of the world where new and more accurate epidemiological data are now available, i.e. China and Europe, as well as on new epidemiological trends that can be suspected from recent case reports and/or from recent changes in animal epidemiology of E. multilocularis infection. The People's Republic of China (PRC) is a newly recognized focus on AE in Asia. Human AE cases were firstly recognized in Xinjiang Uygur Autonomous Region and Qinghai Provinces at the end of 1950s and infected animals were first reported from Ningxia in central China and northeast of Inner Mongolia in the 1980s. E. multilocularis (and human cases of AE) appears to occur in three areas: (1) Northeastern China (northeast focus): including Inner Mongolia Autonomous region and Heliongjiang Province (2) Central China (central focus): including Gansu Province, Ningxia Hui Autonomous Region, Sichuan Province, Qinghai Province and Tibet Autonomous Region and (3) Northwestern China: including Xinjiang Uygur Autonomous Region, bordered with Mongolia, Russia, Kazakhstan and Kyrgyzstan. The highest prevalence of the disease, up to 15 per cent of the population in some villages, is ...